SOCIAL CONSEQUENCES OF CRUELTY OF THE HEART IN QURAN AND HADITH - Mahdi Ghahraman, Leila Bahadori, Samira Ataei Dizaji (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Cruelty of the heart is one of the worst vices that has been condemned in the eyes of Islam. The spread of this vile can have consequences and adverse effects on human life, including its individual and social consequences. In this article, I tried to achieve the social effects and consequences of cruelty by using the library method and searching for verses and narrations, and finally I came to the conclusion that from the point of view of Islamic verses and narrations, cruelty of the heart has bad social consequences, some of which are From: people’s distance from the hard-hearted person, lack of preaching, hindering the implementation of justice and law, not learning from hard-hearted people, lack of faith in the reasoned teachings of the prophets, immorality and disobedience to rational and religious teachings, cutting off divine mercy, distortion and change Divine Word, oppression